Beneficiation of Light Rare Earth Elements from Dubeydib Heavy Mineral Sands Deposits, South Jordan - Twaiq, Osama; Bhatti, Tariq M.; Zaza, Rami; Al-Awah, Hazem (The Nucleus, 2023)
This study describes the beneficiation of monazite mineral from heavy mineral sands deposit of Dubaydib, South Jordan. The heavy mineral sand sample contained 1.80% monazite [(Ce,La,Nd,Th)PO4] based on chemical composition of light rare earth elements such as cerium (Ce), lanthanum (La) and neodymium (Nd). It contained low contents of 0.23% La (0.26% La2O3), 0.50% Ce (0.59% Ce2O3), 0.21% Nd (0.24% Nd2O3), 0.08% Y (0.1% Y2O3), 0.13% Th (0.15% ThO2), 0.015% U (0.018% U3O8) and 0.66% P2O5. The major elemental composition of 64.4% SiO2, 6.9% Al2O3, 6.0% Fe2O3, 6.5% TiO2 and 3.49% Zr (4.72% ZrO2) are present in the sample. The monazite sand sample contained quartz, plagioclase, mica, rutile, Ilmenite and zircon as major minerals with monazite as minor mineral. For beneficiation studies, the density separation (hydrocyclone and Wilfley shaking table) and froth flotation techniques were used to produce monazite concentrates from heavy mineral sand. The produced monazite concentrate-1 contained 5.5% La2O3, 10.6% Ce2O3, 4.8% Nd2O3, 0.54% Y2O3, 0.97% ThO2 and 0.11% U3O8; whereas the concentrate-2 contained 10.3% La2O3, 21.8% Ce2O3, 9.2% Nd2O3 and 1.33% Y2O3.